2019
DOI: 10.2478/hukin-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Post-Activation Potentiation: Is there an Optimal Training Volume and Intensity to Induce Improvements in Vertical Jump Ability in Highly-Trained Subjects?

Abstract: The aim of this study was to compare the acute effects of performing half squats (HSs) with different loading intensities (1, 3, and 5 repetitions maximum [RM], and 60% 1RM) and a different number of sets (1, 2, and 3) on the countermovement jump (CMJ) performance of 18 highly-trained male subjects. Participants were submitted to four experimental conditions (1RM, 3RM, 5RM, and 60% 1RM) in randomized order. The CMJ was assessed before and after each set. Differences in CMJ performance between the distinct expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
1
23
0
4
Order By: Relevance
“… Golas et al (2017) compared five different protocols and they observed statistically significant ( p = 0.01) differences in the RFD and the rate of power development (RPD) ( p = 0.02) in the medium volume load group (80% 1RM) compared to the other conditions. Additionally, Kobal et al (2019) found that a lower volume load with a higher intensity (100% 1RM) protocol induced similar results to a higher volume load and lighter load protocol (93% 1RM and 87% 1RM). Reardon et al (2014) found no performance improvement in any of their protocols (3 sets of either 10 or 3 repetitions with 75% 1RM vs .…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“… Golas et al (2017) compared five different protocols and they observed statistically significant ( p = 0.01) differences in the RFD and the rate of power development (RPD) ( p = 0.02) in the medium volume load group (80% 1RM) compared to the other conditions. Additionally, Kobal et al (2019) found that a lower volume load with a higher intensity (100% 1RM) protocol induced similar results to a higher volume load and lighter load protocol (93% 1RM and 87% 1RM). Reardon et al (2014) found no performance improvement in any of their protocols (3 sets of either 10 or 3 repetitions with 75% 1RM vs .…”
Section: Resultsmentioning
confidence: 60%
“…Of the remaining 8 studies, one analysed the neuromuscular function ( Thomas et al, 2017 ), compared PAP in exercised and contralateral legs ( Andrews et al, 2016 ), compared the relationship between PAP and time under tension ( Krzysztofik et al, 2020 a) and another studied the effects of plyometric PAP in bench press throw ( Krzysztofik and Wilk, 2020 ). The remaining 4 reported contradictory results (Golas et al, 2017 ; Kobal et al, 2019 ; Poulos et al, 2018 ; Reardon et al, 2014 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Esto ha sido explicado por distintos mecanismos fisiológicos como un aumento en la fosforilización de las cadenas ligeras que regulan la miosina, incremento del reclutamiento de unidades motoras de orden superior o también cambios en el ángulo de penación (Healy y Comyns, 2017;Hodgson, Docherty y Robbins, 2005;Tillin y Bishop, 2009). En general, se han utilizado distintos mecanismos para generar el PAP, como pesos libres para realizar back squat o power cleans, pliometría con el peso corporal o utilizando chalecos ponderados, o carreras con trineos de arrastre (Healy y Comyns, 2017), por lo que existen diferencias en cuanto a las cargas, cantidad de repeticiones y tiempo de descanso necesario (Gołaś, Maszczyk, Zajac, Mikołajec & Stastny, 2016;Healy & Comyns, 2017;Kobal et al, 2019;Seitz & Haff, 2016).…”
Section: Introductionunclassified